A critical study of the contents of books in arithmetic in the primary grades in Thailand - Thumchai, Rawiwan 1931- (s.n.], 1963)
This paper presents an examination and evaluation of the arithmetic textbooks written by Joke Sugandhavanij for use in the primary grades I, II, III and IV of schools in Thailand.